Lineage-specific functions of Bcl-6 in immunity and inflammation are mediated through distinct biochemical mechanisms - Huang, Chuanxin (2013)
The transcription factor Bcl-6 orchestrates the germinal center reaction through its actions in B and T cells, and regulates inflammatory signaling in macrophages. We report that genetic replacement by mutant Bcl-6, which cannot bind corepressors to its BTB domain, disrupted germinal center formation and immunoglobulin affinity maturation, due to a defect in B cell proliferation and survival. In contrast, BTB loss of function had no effect on T follicular helper cell differentiation and function, nor other T helper subsets. Bcl6 null mice displayed a lethal inflammatory phenotype, whereas BTB mutant mice experienced normal healthy lives with no inflammation. Bcl-6 repression of inflammatory responses in macrophages was accordingly independent of the BTB domain repressor function. Bcl-6 thus mediates its actions through lineage-specific biochemical functions.